1998
DOI: 10.1002/(sici)1099-081x(199807)19:5<309::aid-bdd108>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plasma butyrylcholinesterase concentration on thein vitro hydrolysis of cocaine in human plasma

Abstract: In humans, the plasma enzyme butyrylcholinesterase, BChE (EC 3.1.1.8), mediates the in vivo plasma hydrolysis of cocaine to the pharmacologically inactive metabolite ecgonine methyl ester, EME. This enzyme has been purified from human plasma to investigate the potential as a treatment for cocaine intoxication. Cocaine (2.1 μg mL−1) was incubated in plasma with a BChE concentration in the normal range (3.02 μg mL−1) and in plasma with enhanced BChE concentrations of 9.14, 20.8 and 37.8 μg mL−1, respectively for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
16
0
4
Order By: Relevance
“…Similarly, the nonspecific sulfonyl‐fluoride AEBSF forms a covalent adduct with the catalytic serine residue of enzymes and renders them inactive. AEBSF at 2 g/l was used for these experiments because esterase activity is high in blood and BuChE concentrations in human plasma are approximately 4 μg/ml 18,19 . AEBSF is soluble in water up to 200, and a 2 g/l final AEBSF concentration allows easy dilution with minimal volume increases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the nonspecific sulfonyl‐fluoride AEBSF forms a covalent adduct with the catalytic serine residue of enzymes and renders them inactive. AEBSF at 2 g/l was used for these experiments because esterase activity is high in blood and BuChE concentrations in human plasma are approximately 4 μg/ml 18,19 . AEBSF is soluble in water up to 200, and a 2 g/l final AEBSF concentration allows easy dilution with minimal volume increases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in cats, Mattes and colleagues showed that pretreatment with BChE prior to cocaine could alter cocaine metabolism, with increased levels of EME observed along with decreased levels of the active metabolite norcocaine [49]. Browne et al [50] showed that human plasma spiked with BChE accelerated the metabolism of cocaine and Carmona et al [51,52] showed that in rats treated with horse serum-derived BChE, the cocaine half-life was significantly reduced. Also using horse serum-derived BChE, Koetzner and Woods showed that cocaine plasma and brain levels in mice were decreased following treatment with the enzyme [53].…”
Section: Bche and Derivativesmentioning
confidence: 99%
“…Addicts have deliberately inhibited BChE with organophosphate pesticides in an attempt to prolong the cocaine "high" (Herschman and Aaron, 1991). Furthermore, there is some evidence from in vitro and animal studies that administration of exogenous BChE may help in the management of cocaine toxicity and addiction (Browne et al, 1998;Carmona et al, 1998Carmona et al, , 2000. It is plausible that inherited BChE deficiency may lead to accumulation of cocaine with repeated cocaine exposure.…”
Section: Cocainementioning
confidence: 99%